(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2018)
Background: Iontophoresis utilizes a transcutaneous process to deliver charged medication to a localized area of injury via an electrical current to remedy pain symptoms. Although this practice is largely used in the physical and occupational therapy settings, there is little evidence showing its use and efficacy in the emergency department as a therapeutic modality. Methods: Through the voluntary enrollment of 39-participants, 21 in the treatment group and 18 serving as controls, subjects were treated via iontophoresis using lidocaine-HCl and dexamethasone or oral NSAID therapy alone. Measurements of pain were numerated in person on the visual-analogue scale (VAS) using a 0-10 range immediately prior to treatment, 30 minutes after treatment, and via phone at 24 and 72-hours after treatment for both groups. Results: At the initiation of treatment, average pain scores for the treatment and control groups were 7.29 and 6.50, respectively. Greater reduction in pain was seen in the iontophoresis group compared to the control group; 62% pain reduction in the iontophoresis group and only 8% reduction in the control group at 30-minutes post-treatment (p<0.001). Similar results were seen at 24 and 72-hours with reductions of 71% and 73% in the experimental group at the respective times versus 18% and 40% reduction in the control group. Further, participants in the control group consumed over 4-times as many oral NSAIDs 24-hours after visiting the emergency department and almost 5-times more oral NSAIDs at 72-hours. At 24-hours the treatment group utilized, on average, less than 1-tablet while the control group had used over 3. At 72-hours, the control group averaged over 6-tablets compared to the less than 2-tablets, on average, for the treatment group. Conclusions: These results are promising in using iontophoresis as an effective treatment modality in the management of acute soft tissue injuries in the emergency department. They not only show greater pain reduction, but iontophoresis reduced the number of oral NSAIDs required for pain relief, lowering the complications associated with these medications.